A parametric analysis of rectangular rib roughened triangular duct solar air heater using computational fluid dynamics. (15th November 2017) - Kumar, Rajneesh; Kumar, Anoop; Goel, Varun
Highlights: Flow characteristics and heat transfer has been examined for roughened SAH. The absorber plate of SAH is roughened with rectangular shape roughness. New roughness parameter (Rib Aspect Ratio) has been introduced and examined. Heat transfer augmentation considerably varies by changing roughness parameter. Abstract: Solar air heater (SAH) absorbs thermal radiations from Sun and utilizes it to heat air. The thermal performance of SAH can be improved by using ribs on the absorber plate. In this paper, rectangular geometry of ribs is considered over the absorber plate. The fluid flow characteristics and heat transfer in ribbed triangular duct (with an apex angle of 60°) SAH is analyzed using computational fluid dynamics ( CFD ). The roughened side of duct is subjected to a constant heat flux of 1000 W m −2, whereas, roughness elements are adiabatic in nature. The three-dimensional model of SAH is developed and numerical simulations are carried out by developing CFD code with the help of finite volume method. The numerical simulations are performed on commercial ANSYS Fluent 12.1 software. A new roughness parameter called rib aspect ratio ( e / w ) is introduced in this study and its effect on friction factor ( f ) and Nusselt number ( Nu ) is investigated along with relative roughness height ( e / D ) and relative roughness pitch ( P / e ) for the Reynolds number ranges from of 4000 to 18, 000. The values of rib aspect ratio ( e / w ), roughness height ( e / D ) and relative roughness pitch ( P / e ) range from 0.25 to 4.0, 0.02 to 0.04 and 5 to 15, respectively. A considerable increase in friction factor ( f ) and Nusselt number ( Nu ) is observed due to rectangular rib in comparison to smooth one. The numerically predicted results are compared with the available results and a good agreement between them is observed with maximum error of ±4.04%. A significant variation in friction factor ( f ) and Nusselt number ( Nu ) is observed by varying rib aspect ratio ( e / w ) values from 0.25 to 4.0. The maximum value of thermohydraulic performance parameter (TPP) is found 1.89 in case of relative roughness pitch ( P / e ), rib aspect ratio ( e / w ) and relative roughness height ( e / D ) value of 10, 4.0 and 0.04, respectively, at the Reynolds number ( Re ) of 15, 000.